Deep sequencing reveals abundant noncanonical retroviral microRNAs in B-cell leukemia/lymphoma - Rosewick, Nicolas; Momont, Mélanie; Durkin, Keith; Takeda, Haruko; Caiment, Florian; Cleuter, Yvette; Vernin, Céline; Mortreux, Franck; Wattel, Eric; Burny, Arsène; Georges, Michel; Van den Broeke, Anne (Proceedings of the National Academy of Sciences - PNAS, 2013)
Viral tumor models have significantly contributed to our understanding of oncogenic mechanisms. How transforming delta-retroviruses induce malignancy, however, remains poorly understood, especially as viral mRNA/protein are tightly silenced in tumors. Here, using deep sequencing of broad windows of small RNA sizes in the bovine leukemia virus ovine model of leukemia/lymphoma, we provide in vivo evidence of the production of noncanonical RNA polymerase III (Pol III)-transcribed viral microRNAs in leukemic B cells in the complete absence of Pol II 5′-LTR–driven transcriptional activity. Processed from a cluster of five independent self-sufficient transcriptional units located in a proviral region dispensable for in vivo infectivity, bovine leukemia virus microRNAs represent ∼40% of all microRNAs in both experimental and natural malignancy. They are subject to strong purifying selection and associate with Argonautes, consistent with a critical function in silencing of important cellular and/or viral targets. Bovine leukemia virus microRNAs are strongly expressed in preleukemic and malignant cells in which structural and regulatory gene expression is repressed, suggesting a key role in tumor onset and progression. Understanding how Pol III-dependent microRNAs subvert cellular and viral pathways will contribute to deciphering the intricate perturbations that underlie malignant transformation.